INFECTION AND IMMUNITY: STRATEGIES FROM BOTH SIDES - G. F. Zheleznikova (Медицинская иммунология, 2014)
Abstract. The review considers contemporary data concerning the mechanisms of interaction between infectious agents and host immune system. The ways for evasion of the host immune reactions are described, and “behavioral” patterns are provided for particular pathogens, e.g., viruses, bacteria, protozoa, helminthes. The diversity of cells and soluble mediators participating in the immune response is discussed.